2020
DOI: 10.3390/en13061461
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Wind Power Plant Modernization

Abstract: The production of energy in wind power plants is regarded as ecologically clean because there being no direct emissions of harmful substances during the conversion of wind energy into electricity. The production and operation of wind power plant components make use of the significant potential of materials such as steel, plastics, concrete, oils, and greases. Energy is also used, which is a source of potential negative environmental impacts. Servicing a wind farm power plant during its operational years, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 60 publications
(89 reference statements)
1
10
0
Order By: Relevance
“…GWP of the production/manufacture stage is 94%. As a matter of fact, in line with past studies [11,[16][17][18][19][20][21][22][23][24][25], Tables 1 and 2 show the largest GWP contribution comes from the production/manufacture stage in wind turbines. It can be decreased using alternative materials with the lowest CO 2 emissions or reducing the amounts of concrete and steel for the production/manufacture stage.…”
supporting
confidence: 85%
See 2 more Smart Citations
“…GWP of the production/manufacture stage is 94%. As a matter of fact, in line with past studies [11,[16][17][18][19][20][21][22][23][24][25], Tables 1 and 2 show the largest GWP contribution comes from the production/manufacture stage in wind turbines. It can be decreased using alternative materials with the lowest CO 2 emissions or reducing the amounts of concrete and steel for the production/manufacture stage.…”
supporting
confidence: 85%
“…The results of Bhandari et al highlighted a correlation between the GHG to the AEY for onshore wind farms and single wind turbines. Kasner et al [25] investigated the energy efficiency and environmental effects of wind turbines with a lifespan of 25 years and 50 years, using the sustainable modernization method. To increase the lifetime of the wind turbine to 50 years, it was extended by replacing components, such as rotor, blades, structure parts etc., and maintaining them at the required time.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The recycling of plastics makes it possible to significantly reduce the environmental burden during the life cycle and to recover some of the natural resources and energy [ 21 , 22 ]. Previous studies [ 14 , 18 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ] have shown that for multi-plastic components from which it is difficult to separate individual materials (e.g., wind turbine blades, automobile tires), the use of recycling as a form of post-consumer management significantly contributes to the reduction of environmental impacts during the life cycle of these components.…”
Section: Introductionmentioning
confidence: 99%
“…Researching, developing, and assessing the technological readiness of an innovative ribbon turbine using NASA's TRL method falls in line with the realization of intelligent development goals laid out in the "Europe 2020 Strategy for Development" [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%